Features of re-entrant albedo deuteron trajectories in near Earth orbit with PAMELA experiment. Issue 3 (January 2016) - Koldobskiy, S A; Adriani, O; Barbarino, G C; Bazilevskaya, G A; Bellotti, R; Boezio, M; Bogomolov, E A; Bongi, M; Bonvicini, V; Bottai, S; Bruno, A; Cafagna, F; et al.
Abstract: The results of trajectory reconstruction for re-entrant albedo deuteron fluxes obtained in the PAMELA experiment are presented in this work. PAMELA is an international experiment aimed on measurements of cosmic ray particle fluxes in wide energy range. In particular, analysis of PAMELA data gives possibility to identify deuterons. Classification of re-entrant albedo deuterons with energies from 70 to 400 MeV/nucleon depending on theirs reconstructed lifetimes and generation zones is presented here at first time.